Efek dan Pencegahan Pernikahan Dini Pada Remaja: Studi Literatur - Hardiyati, Hardiyati; Hasir, Hasir; Supratti, Supratti (Jurnal Kebidanan Malakbi, 2023)
Marriage is a very sacred thing and maintains the integrity of the family by looking at several aspects of a person's physical, spiritual and psychological aspects that support happiness. Early marriage is marriage that has not reached the age of 18 years. This is referred to as one of the social pathologies that cause or poverty. The Sustainable Development Goals (SDGs) on education, maternal health, poverty, women's empowerment and human rights cannot be achieved if the problem of early marriage is not addressed in many low and medium prayer countries. The results of the investigation of the literature study from these 15 articles can be described that the occurrence of early marriage can be caused by several factors, namely economic problems, customs, education, decision makers are parents, living in rural areas. Some of the effects that can occur in early marriage are domestic violence, psychosocial burden and stress, reduction, illness, women's independence, health of mothers and children, and the level of school activity of children. Intervention efforts that can be made are increasing education and knowledge, media exposure, peer education methods, involving religious shops, social in educational activities for adolescents. From the results of this literature study, it can provide an understanding of the development and prevention of early marriage and seek therapeutic and comprehensive preventive measures.